ENSURING MANAGEMENT OF THE DEPLOYMENT OF THE MOBILE COMPONENT OF THE COMMUNICATION SYSTEM OF UNITS AND PARTS OF THE NATIONAL GUARD OF UKRAINE WITH DIGITAL RADIO EQUIPMENT - Tymchenko, Serhii; Lazarev, Viktor; Mayboroda, Ihor (Honor and Law, 2023)
The capabilities of modern Harris RF-7800S-TR digital radios for managing communication units are considered. A comparative analysis of the capabilities of the Motorola DP4800 and Harris RF-7800S-TR radio stations was carried out in providing control over the deployment of the mobile communication center of the auxiliary control point of the territorial control of the National Guard of Ukraine. Proposed recommendations for the implementation of the topology of the Harris RF-7800S-TR radio station programming file for the management of the process of deploying a field communication node on one operating frequency with the separation of all radio networks and ensuring their simultaneous operation independently of each other and with access only to the appropriate management levels. The research results make it possible to develop an innovative frequency plan for the deployment control system of the auxiliary control point field communication node. At the same time, all radio stations operate on the same frequency, using different positions of the radio station channel switch. Separation of radio networks is temporary, and access to radio networks is carried out using various tangents, the functions of which are programmed in advance. Thus, the modern Harris RF-7800S-TR digital radio station, which is in service with NSU units, allows for reliable management of the deployment of a field communication node with the fulfillment of all requirements for security, communication security, and with minimal expenditure of material resources, and the conducted class on the implementation of the topology of the radio station programming file will provide the most effective training of communication specialists for positions in the military.